Supervisi Klinis Berbasis Direct Instruction untuk Meningkatkan Kompetensi Guru dalam Menggunakan Model-Model Pembelajaran di SDN 11/X Nipah Panjang Semester Ganjil Tahun Ajaran 2021/2022 - Kartini Kartini (Departement of Mathematics Education, 2023)
The purpose of this study is to obtain information and discuss the application of direct instruction-based clinical supervision to increase teacher competence in using learning models at SDN 11/X Nipah Panjang odd semester of the 2021/2022 academic year. This research is a school action research conducted at SDN 11/X Nipah Panjang in the odd semester of the 2021/2022 academic year. The research subjects were all teachers at SDN 11/X Nipah Panjang, totaling 7 people who were class I to class VI teachers and PAI teachers at SDN 11/X Nipah Panjang. Data was collected through observation sheets, field notes, and documentation. Data analysis techniques use percentages and data reduction. Based on the results of the research and discussion, it can be concluded that through the application of direct instruction-based clinical supervision, it can increase teacher competence in applying the learning model at SDN 11/X Nipah Panjang by means of random appearances.